1991
DOI: 10.1002/jez.1402570113
|View full text |Cite
|
Sign up to set email alerts
|

Vitellogenin purification and development of assay for vitellogenin receptor in oocyte membranes of the tilapia (Oreochromis niloticus, linnaeus 1766)

Abstract: An assay has been successfully developed for vitellogenin receptors in isolated oocyte membranes of the tilapia (Oreochromis niloticus). Vitellogenin produced by estrogen stimulation of the male tilapia was purified by anion-exchange chromatography on DEAE-Sephacel and identified by its incorporation of 32P-orthophosphate and 3H-leucine in vivo. Only one molecular form of vitellogenin was found to be induced by estrogen treatment. After iodination with Iodogen, the 1251-vitellogenin was shown to be immunologic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
19
0
2

Year Published

1992
1992
2012
2012

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(25 citation statements)
references
References 29 publications
4
19
0
2
Order By: Relevance
“…Scatchard analysis of the saturation data (fig 3, inset) (Chan et al, 1991), and from 1.3 to 3.5 nM (Lancaster and Tyler, 1994) or 10 to 30 nM (Nunez Rodriguez et al, 1996) (lane 4).…”
Section: Autoradiographymentioning
confidence: 97%
“…Scatchard analysis of the saturation data (fig 3, inset) (Chan et al, 1991), and from 1.3 to 3.5 nM (Lancaster and Tyler, 1994) or 10 to 30 nM (Nunez Rodriguez et al, 1996) (lane 4).…”
Section: Autoradiographymentioning
confidence: 97%
“…The functionality of Vtgr in fish has been examined in studies with Coho salmon [13], Nile tilapia [14], and seabass [15]; these studies focused on Vtg uptake through implementation of binding assays that demonstrated the presence of surface receptors within oocyte membranes. Furthermore, the existence of a new system of multiple Vtgrs that disparately bind functionally different types of Vtgs in white perch has been suggested [16].…”
Section: Introductionmentioning
confidence: 99%
“…In teleosts, the presence of receptor-mediated endocytosis has also been demonstrated (Selman and Wallace 1982;Tyler et al 1988;Kanungo et al 1990). Recently, Chan et al (1991) have characterized a vitellogenin receptor in oocyte membranes of tilapia, Oreochromis niloticus. Vitellogenin has been isolated and characterized from a variety of fishes, including two species of tilapia, 0. aureus (Ding et al 1989) and 0. niloticus (Chan et al 1991).…”
Section: Introductionmentioning
confidence: 99%
“…Recently, Chan et al (1991) have characterized a vitellogenin receptor in oocyte membranes of tilapia, Oreochromis niloticus. Vitellogenin has been isolated and characterized from a variety of fishes, including two species of tilapia, 0. aureus (Ding et al 1989) and 0. niloticus (Chan et al 1991). In circulation, the vitellogenin molecule is known to be present mainly as a dimer with a molecular mass ranging from 300 kDa in tilapia, 0. aureus (Ding et al 1989), to 600 kDa in chum salmon, Oncorhynchus keta, and rainbow trout, Oncorhynchus mykiss (Hara 1978;Hara and Hirai 1978).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation